Opioid prescription patterns and pain severity among patients with opioid use disorder and other substance use disorders: a mixed methods study - Erin F. Madden; Gintare Daulys; Benjamin Tingey; Felicia Frabis; Pooja Lagisetty; Philip J. Kroth; Fares Qeadan (PAIN Reports)
Abstract. Objective:. Pain management for patients with substance use disorders (SUDs) poses challenges, yet little is known about their pain severity perceptions. We conducted a mixed-methods study to understand numeric pain severity reporting among patients with SUD. We assessed how interactions between opioid prescribing and time, medications for opioid use disorder (MOUD), complementary medicine (CM), and outpatient SUD-related services (OS) predict differences in reported pain severity among patients with SUD. Methods:. We analyzed electronic health records (EHR) data, from 2003 to 2023, among the Oracle EHR Real-World Database, which comprised 141 US health systems from 50 states. We used longitudinal patient-reported numeric rating scale pain severity scores in linear mixed effects regressions to predict mean pain severity scores. We also conducted 2 focus-groups, from 2022 to 2023, with patients with SUD and SUD-treating clinicians aiming to explore pain severity reporting. Results:. Overall, predicted mean pain scores (95% confidence interval) were highest for patients with OUD (4.52 [4.51, 4.53]), lower for other patients with SUD (3.80 [3.79, 3.81]), and lowest for controls (3.28 [3.27, 3.29]) across all opioid prescription doses and durations. Complementary medicine use was associated with lower pain scores for all patients prescribed opioids. Pain scores were also lower for patients with OUD and SUD prescribed opioids and using OS, and for patients with OUD treated with MOUD and prescribed higher dose opioids. Focus-groups revealed pain reporting is influenced by anticipated clinician disbelief, treatment changes, and stigma. Conclusion:. These findings highlight the need to address pain within addiction treatment and further examine effective pain management interventions for this complex patient population.